KOTEKS DALAM WACANA POLITIK JAWA POS EDISI MEI 2016 - Sriyanto (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
This study was conducted to describe contexts words, phrases, and sentences on political discourse Jawa Pos May issue 2016. This research data sourced from Jawa Pos dated from 13-19 May 2016. The data collected by reading and analyzing data catat.Teknik using critical discourse analysis models Fairclough. There are three steps in the data analysis, namely: description, interpretation and explanation. The existence of contexts in a discourse has a relationship with other texts. Contexts word on research in the form of nominal words, verbs, and adjektifa. Contexts phrase is a construction unit consisting of two or more words that form a single unit and pose a new meaning. Contexts sentence on research data, in the form of a single sentence and compound sentence. In order words related to each other, need the presence of a marker / tool that can relate. When the marker was born interlock shape, it is called cohesion relationship. And, if the relationship is established by considering the meaning, then this is called coherent.